Produksi Tanaman Jagung Manis (Zea Mays L. Saccharata) yang Diperlakukan dengan Kompos Kascing dengan Dosis yang Berbeda - Marvelita, Awalita; Darmanti, Sri; Parman, Sarjana (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2006)
Land where as place growth plant must have nutrient content for support plant production. Available nutrient on soil must influence on organic substrate, because organic substrat can repairing of soil plant. Organic content in soil was decrease for a long time, it cant solution with given fertilizer. This research used organic fertilizer as cascing fertilizer with application on corn ( Zea mays L Saccarata ) plant. Main research is understand the influence of fertilizer of kascing with different dosage on production of sweet corn and understanding optimally dosage on maximally production of sweet corn. This research used RAL single factor, 4 treatment is dosage 0 gr/plant ( DO ), 125 gr/plant ( D1 ), 240 gr/plant ( D2 ), and 375 gr/plant ( D3 ). Data analysis with anova and continued by Duncan’s Multiple Range Test ( DMRT ) on level of signification 5%. Result this research indicatet that production sweet corn by treatment D1, D2, and D3 more lower compare with D0. This fact because the use fertilizer have highly ratio C/N, that hight nutrition that used by plant can’t on ready form.